Weight-related concerns and weight-control behaviors among overweight adolescents in Delhi, India: A cross-sectional study - Stigler, Melissa H (BioMed Central, 2011)
BACKGROUND: Obesity is emerging as a public health problem among adolescents in India. The aim of this study was to describe specific weight-related concerns among school-going youth in Delhi, India and to assess the prevalence of weight control behaviors, including healthy and unhealthy ones. Differences by weight status, gender, grade level, and school-type (a proxy for SES in this setting) are considered. METHODS: This study is cross-sectional by design. A sample of eighth and tenth graders (n = 1818) enrolled in Private (middle-high SES) and Government (low SES) schools (n = 8) in Delhi, India participated. All students' height and weight were measured. Students participated in a survey of weight-related concerns and weight-control behaviors, as well. Mixed-effects regression models were used to test for differences in weight-related concerns and weight-control behaviors across key factors of interest (i.e., weight status, gender, grade level, and SES). RESULTS: The combined prevalence of obesity and overweight was 16.6%, overall. Controlling one's weight was important to overweight and non-overweight youth, alike (94.2% v. 84.8%, p < 0.001). Significantly more overweight or obese youth reported trying to control their weight last year, compared to those who were not overweight (68.1% v. 18.0%, p < 0.001). Healthy weight control behaviors were more common than unhealthy or extreme practices, although the latter were still prevalent. Half of the overweight or obese students misclassified their weight status, while about 1 in 10 non-overweight youth did the same. Body dissatisfaction was highest among overweight youth and girls. CONCLUSIONS: Interventions to promote healthy weight control should be pertinent to and well-received by school-going youth in India. Healthy weight control practices need to be explicitly encouraged and unhealthy practices reduced. Future interventions should address issues specific to body image, too, as body dissatisfaction was not uncommon among youth.